(untitled) (Società e diritti, 2024)
NPOs participate in the management of activities and services of general interest, in a new relationship of collaboration with the PA, inspired by horizontal subsidiarity. They stand beyond the market, but before the public sector, and cannot therefore fall under the ordinary regulations – that were designed for entities that instead operate in the market. Since they stand alongside the public administration in the care of general interests, NPOs do not properly contribute to public expenditures: they directly provide for the activities that those expenditures should finance, instead. The discipline of the income tax reflects this new arrangement, whereby tax concessions mostly concern indirect taxation and private persons supporting these entities.